CAN MOTIVATIONAL INTERVIEWING REDUCE VIDEO GAME ADDICTION? VIEWED FROM: REGULATORY FOCUS THEORY AND INTERPERSONAL COMPETENCE - Nugraha, Yudhi Purwa; Fitri Uswatun Khasanah (SMA Trensains Muhammadiyah Sragen, 2023)
The positive effects of the video game industry have contributed a lot. But the negative effects of video game addiction need to be reduced. Cognitive Behavioral Therapy (CBT) is a commonly used approach to reduce video game addiction. However, CBT does not encourage the emergence of intrinsic motivation within oneself, so that individuals can relapse into video game addiction behavior. Empirically the Motivational Interviewing (MI) approach is able to bring out individual intrinsic motivation to reduce addictive behavior. The causes of addictive behavior need to be understood in a heterogeneous and comprehensive manner. Video game addiction factors are categorized into psychological factors, internal factors, and external factors. This research was limited to video game addiction factors in terms of internal Regulatory Focus Theory (RFT) factors and external factors of interpersonal competence. The aim of the study was to test the effectiveness of the MI approach on a group of adolescent subjects by reviewing RFT and interpersonal competence. This study uses instruments that have been adapted. The hypothesis test uses a three-way analysis of variance (ANOVA). The general results of the MI approach did not show a significant difference compared to group counseling using other approaches. However, in particular the MI approach for development focus members and high interpersonal competence has significant differences compared to prevention focus members with high or low interpersonal competence.